THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION - Zulfina Arizky Zulkifly; Haris Maupa; Andi Nur Bau Massepe (Paulus Journal of Accounting (PJA), 2023)
The purpose of this research is to analyze and explain the effect of product quality and service quality on customer satisfaction at Pancious CafÃ©. The type of research used is explanatory research. The sample in this study was 100 Pancious CafÃ© customers. The sampling technique uses systematic random sampling. Data collection method with a questionnaire. Data analysis using multiple linear regression analysis. The results showed that there was a significant influence between product quality on customer satisfaction and service quality on customer satisfaction, with a sig value < 0.05.